Evaluation of bipolar radiofrequency ablation for occluded self-expandable metal stents in the bile duct: in vivo and in vitro study - Yoon, Won Jae; Kim, Yong-Tae; Daglilar, Ebubekir S.; Mino-Kenudson, Mari; Brugge, William R. (Endoscopy, 2015)
Background and aims: Endobiliary radiofrequency ablation (RFA) has been used to treat occluded self-expandable metal stents (SEMSs). The aim of this study was to determine the characteristics of bipolar RFA in occluded SEMSs using both in vivo and in vitro models.Methods: For the in vivo study, uncovered SEMSs were deployed in the bile ducts of three pigs; another pig was used as the control. RFA was performed at 10 W for 90 seconds. The bile duct was examined for histological changes. For the in vitro simulation of tissue ingrowth in SEMSs, RFA at 10 W for 30 seconds was performed on SEMS-occlusion polyacrylamide-gel phantoms.Results: The ablation depth was markedly reduced in the stented porcine bile duct. RFA of uncovered SEMS-occlusion gel phantoms resulted in early termination of RFA when the coagulated area contacted the SEMS. This phenomenon was not observed in RFA of the covered SEMS-occlusion gel phantoms.Conclusions: The presence of SEMSs attenuated the effect of bipolar endobiliary RFA. Tumorous tissue outside the SEMS is unlikely to be affected.